Photo-double-ionization of H2: Two-center interference and its dependence on the internuclear distance - Schöffler, M. S.; Kreidi, K.; Akoury, D.; Jahnke, T.; Staudte, A.; Neumann, N.; Titze, J.; Schmidt, L. Ph. H.; Czasch, A.; Jagutzki, O.; Costa Fraga, R. A.; Grisenti, R. E.; et al. (My University, 2008)
We investigate photo-double-ionization of H2 by circular polarized photons at hν=160eV. The previously observed two-center interference pattern in the angular distribution of the electron sum momentum is shown to depend strongly on the internuclear distance and the summed electron momenta.